Intraventricular Delivery of siRNA Nanoparticles to the Central Nervous System - Rishab Shyam; Yong Ren; Jason Lee; Kerstin E Braunstein; Hai-Quan Mao; Philip C Wong (Elsevier, 2015)
Alzheimer's disease (AD) is a progressive neurodegenerative disease currently lacking effective treatment. Efficient delivery of siRNA via nanoparticles may emerge as a viable therapeutic approach to treat AD and other central nervous system disorders. We report here the use of a linear polyethyleneimine (LPEI)-g-polyethylene glycol (PEG) copolymer-based micellar nanoparticle system to deliver siRNA targeting BACE1 and APP, two therapeutic targets of AD. Using LPEI-siRNA nanoparticles against either BACE1 or APP in cultured mouse neuroblastoma (N2a) cells, we observe selective knockdown, respectively, of BACE1 or APP. The encapsulation of siRNA by LPEI-g-PEG carriers, with different grafting degrees of PEG, leads to the formation of micellar nanoparticles with distinct morphologies, including worm-like, rod-like, or spherical nanoparticles. By infusing these shaped nanoparticles into mouse lateral ventricles, we show that rod-shaped nanoparticles achieved the most efficient knockdown of BACE1 in the brain. Furthermore, such knockdown is evident in spinal cords of these treated mice. Taken together, our findings indicate that the shape of siRNA-encapsulated nanoparticles is an important determinant for their delivery and gene knockdown efficiency in the central nervous system.